2012
DOI: 10.1016/j.neuroimage.2011.12.057
|View full text |Cite
|
Sign up to set email alerts
|

Left hemisphere plasticity and aphasia recovery

Abstract: A recent study by our group revealed a strong relationship between functional brain changes in the left hemisphere and anomia treatment outcome in chronic stroke patients (N=26) with aphasia (Fridriksson, 2010). The current research represents a continuation of this work in which we have refined our methods and added data from four more patients (for a total sample size of 30) to assess where in the left hemisphere treatment-related brain changes occur. Unlike Fridriksson (2010) which only focused on changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
158
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(186 citation statements)
references
References 68 publications
17
158
0
6
Order By: Relevance
“…With respect to recovery, some studies demonstrate that right hemisphere compensation is responsible for improvement in language over time (e.g., Rosen et al, 2000), while others show perilesional activity or involvement of other undamaged areas in the lesioned hemisphere (e.g., Fridriksson, Richardson, Fillmore, & Cai, 2012). Most studies reveal a mixture of these patterns (for reviews, see Crinion & Leff, 2007;Thompson & den Ouden, 2008).…”
Section: Functional Neuroimagingmentioning
confidence: 99%
“…With respect to recovery, some studies demonstrate that right hemisphere compensation is responsible for improvement in language over time (e.g., Rosen et al, 2000), while others show perilesional activity or involvement of other undamaged areas in the lesioned hemisphere (e.g., Fridriksson, Richardson, Fillmore, & Cai, 2012). Most studies reveal a mixture of these patterns (for reviews, see Crinion & Leff, 2007;Thompson & den Ouden, 2008).…”
Section: Functional Neuroimagingmentioning
confidence: 99%
“…In studies of Hamilton et al 37 and Martin et al 38 , the stimulation protocols were applied in three subjects (one and two, respectively) with chronic aphasia (more than a year). The results were significant for the improvement of the language in the case of the study in 2010 and for one of the participants of the study in 2009, indicating that the same protocol may not produce the improvement of language for all patients, depending mainly of injured areas, issue discussed by Martin, et al 38 , and indicated in the Sarasso et al 18 , Fridriksson et al 21 and Fridriksson et al 22 studies. Jung et al 29 and Naeser et al 39 aimed to study the rehabilitation of speech in a case of Global Aphasia with the right dominant hemisphere, and non-fluent Aphasia associated with sleep apnea.…”
Section: Treatments With Repetitive Trans Cranial Electric Stimulatiomentioning
confidence: 78%
“…Among the studies whose objective was to investigate the recovery of a specific language ability, two examined the relationship between the improvement in the ability of naming, the cerebral activation 22 and the extension of the lesion 23 . Both studies involved 20 participants on average, with fluent and non-fluent aphasia, and used the techniques of semantic, phonological and gestures facilitators, which were compared among them.…”
Section: E Assessment Of Methodological Rigormentioning
confidence: 99%
“…It has been previously suggested that the degree of impairment and plasticity in the white matter fiber tracts relevant to language processing is also of great importance in predicting the recovery of language function (Naeser, Palumbo, Helm-Estabrooks, Stiassny-Eder, & Albert, 1989;Schlaug, Marchina, & Norton, 2009). Besides, language and speech therapy can lead to the reorganization of language neural networks accounting for brain plasticity in stroke survivors (Fridriksson, Richardson, Fillmore, & Cai, 2012) even at the chronic phase (Meinzer et al, 2004). However, the information of language and speech therapy was not available in most cases reported in the present study and thus, we could not address its effects on language recovery.…”
Section: Discussionmentioning
confidence: 99%